THE IMPACT OF POWER OUTAGES IN MEDAN CASE STUDY: COMMUNITY, MERCHANT, OFFICE & INDUSTRY - Istu Sri Poneni (Buletin Utama Teknik, 2018)
This study aims to determine the impact of power cuts towards people, small businessmen, officers, and industries in the city of Medan . This research uses  method of data through interviews, and questionnaires were addressed to 2 entrepeneures, 2 common people, 2 small businessmen, and 2 officers purposively selected to determine the location of the research is also done intentionally ( purposive sampling ) . The analysis technique used in this study is a multiple linear regression analysis and descriptive analysis for each problem using SPSS 20. The data used in this study are primary. The results of this study indicate that a power outages has negative and direct impact towards people, small businessmen, officers, and industries in the city of Medan.